The Significance of Linguistics in the Study of Philosophy - Istikomah Istikomah; Nurhayati Nurhayati (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
Since the era of Greece and Rome in the 4-2 century BC, until this Postmodern one, language has been one of the most central and core issues of philosophical studies. Language and Philosophy both focus on issues related to structure and meaning in natural language, as discussed in the philosophy of language and other disciplines, among others; philosophical theories about meaning and truth, presuppositions, implicatures, speech acts, etc. This article discusses several case studies that illustrate the relationship between the philosophy of language through three branches of linguistics; syntax (Stanley, 2000), semantics (von Fintel, 2001), and pragmatics (Potts, 2005). The results of the study reveal a significance and interdependence between philosophy and language. Philosophy requires language as a means of communicating ideas and also as an object of study in philosophy. Meanwhile, language also badly needs philosophy as a means or method to analyze systematically to get solutions to solving linguistic problems.Keywords: linguistics, philosophy, syntax, semantics, and pragmatics